ANALISIS POTENSI SERAPAN KARBON DI KAWASAN ARBORETUM FAKULTAS KEHUTANAN UNIVERSITAS LANCANG KUNING - Mariana Mariana; Ermina Sari; Jumiati Jumiati; Marta Dinata (Program Pascasarjana Universitas Riau, 2016)
This study aims to determine the value of the index of species diversity in vegetation Arboretum Arboretum and analyze potential as a carbon sink. This research was conducted at the Faculty of Forestry Arboretum Pekanbaru Lancang Kuning University Academic Year 2015/2016, data collection was conducted in December 2015 - January 2016. The method used in this research is the method of plot or squares that are distributed on a line (transect). Squares method which is one method used in analyzing the state of the vegetation (Soerianegara & Indrawan, 2005). Results of research conducted in the Arboretum area of data showed that the vegetation is dominated by mature trees Pulai (Alstonia scolaris) and spoons (Endospermum diadenum). Vegetation is dominated by small trees bloody (Myristica inners). At the seedling stage is dominated by red fowl (Palaquium burckii). Potential carbon uptake reached 2301.83 / ha. It can be concluded that the value of the index constituent species diversity of vegetation tend to be categorized Arboretum high and has a great potential to absorb carbon